Pengaruh Pembelajaran Mix Models (Teams Games Tournaments and Auditory Intellectually Repetition) Terhadap Hasil Belajar Matematika Ditinjau dari Motivasi Belajar - Fatimah Akbal; Alimuddin; Rusli (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This research was quasi-experimental which aims to know the influence of mix models learning (TGT-AIR) towards mathematics learning outcomes viewed from learning motivation. The population in this research was Eighth-grade students at one of Junior High School in Makassar. The sample consisted of two classes, namely class VIII-2 that gave treatment by using mix models learning (TGT-AIR), and class VIII-10 as a comparison class taught by using direct learning model selected by cluster random sampling technique. The variables in this research were learning models, learning motivation, and mathematics learning outcomes. The research instruments used were observation sheets, questionnaires about leaning motivation in mathematics, and mathematics learning outcomes tests. The data obtained were analyzed in descriptive and inferential through t-test for two independent samples. Based on the results of the t-test, it was found that: (a) there was a difference of mix models learning (TGT-AIR) and direct learning model on mathematics learning outcomes; (b) there was an effect of motivation on students' mathematics learning outcomes in the implementation of mix models learning (TGT-AIR); (c) there was no effect of motivation on students' mathematics learning outcomes in the implementation of direct learning model, (d) there was a difference of mix models learning (TGT-AIR) and direct learning model on mathematics learning outcomes for students who are highly motivated in learning; and (e) there was no difference of mix models learning (TGT-AIR) and direct learning model on mathematics learning outcomes for students who are low motivated in learning.